2012
DOI: 10.5491/shaw.2012.3.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Blood and Body Fluid Exposure Related Knowledge, Attitude and Practices of Hospital Based Health Care Providers in United Arab Emirates

Abstract: ObjectivesKnowledge, attitudes, and practices of healthcare providers related to occupational exposure to bloodborne pathogens were assessed in a tertiary-care hospital in Middle East.MethodsA cross-sectional study was undertaken using a self-administered questionnaire based on 3 paired (infectivity known vs. not known-suspected) case studies. Only 17 out of 230 respondents had an exposure in the 12 months prior to the survey and of these, only 2 had complied fully with the hospital's exposure reporting policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…All health care workers who experience any form of occupational exposure to blood or other body fluids and tissues of patients, which may contain pathogens that are transmitted by blood (especially HBV, HCV and HIV), should be reported to elected family medicine practitioner and responsible occupational medicine institution (11). A recent pilot study conducted in Croatian hospitals (9) showed that only approximately 5% of health workers in Croatia reported stab incidents and exposure to blood or infections that are transmitted by blood, which means that approximately 95% of incidents of this kind remain unreported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All health care workers who experience any form of occupational exposure to blood or other body fluids and tissues of patients, which may contain pathogens that are transmitted by blood (especially HBV, HCV and HIV), should be reported to elected family medicine practitioner and responsible occupational medicine institution (11). A recent pilot study conducted in Croatian hospitals (9) showed that only approximately 5% of health workers in Croatia reported stab incidents and exposure to blood or infections that are transmitted by blood, which means that approximately 95% of incidents of this kind remain unreported.…”
Section: Discussionmentioning
confidence: 99%
“…In our sample the situation is slightly better 21%, but no one reported the incident to the occupational medicine institute which needs to prevent occupational hazard. It should be noted that only those who report incidents receive appropriate evaluation and treatment after the exposure, which means that the others had not even been offered to appropriate assessment and management of risks after exposure (11, 13). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] Failure to report an exposure increases the likelihood of consequential infection by precluding testing of source patient for BBIs and post-exposure prophylaxis (PEP) to the exposed person. [4] In addition, formal reporting of exposures is required for generation of data for formulating a uniform national policy for the prevention and treatment of occupationally acquired BBIs. OEs can be prevented or reduced by observing “universal precautions” (UPs) and employing safe strategies at workplace.…”
Section: Introductionmentioning
confidence: 99%